Fuzzy logic track control of an automated lawnmower - Kayode, Ajayi Oluwaseun; Ishola, Balogun Daud; Olubunmi, Ige Ebenezer; John, Adeyi Abiola (Institute of Advanced Engineering and Science, 2022)
Automation of agricultural and horticultural operations keeps received great attention for over a decade. The control parameters adopted depend on the location and characteristics of likely obstacles and navigation requirements. An automated lawnmower (ALM) with fuzzy logic control is presented in this study. Fuzzy logic was chosen to improve a previous work which was controlled via Bluetooth. Three ultrasonic sensors and two proximity sensors served as the eyes of the ALM for navigation and obstacle avoidance while the cutting blade was made of stainless steel and controlled by a brushless direct current (BLDC) motor. A fuzzy algorithm was implemented on an Arduino controller with the inputs and outputs as directional instructions. Obstacle avoidance was achieved by setting a range of values for the sensors interpreted by the fuzzy logic for the corresponding output in the form of navigations. Three trials tests were conducted on the ALM on a 5 m2 portion of land with an average grass height of 0.09 m. The average cut area was 4.46 m2, therefore achieving an efficiency of 89.2%, which is highly productive. It was observed that the power consumption was minimal compared to the previous design because at the end of the three trials 46% of the battery was left after over 3 hours of operation.